Development of Learning Media for Hydroponic Systems Based on the Internet of Things - Arief, Ulfah Mediaty; Afdam, Delano Hafis; Sukamta, Sri; Dzulfikar, Andi Muhammad; Yarman, Indah Novi; Widiatningrum, Talitha; Baswara, Satsya Yoga; Prasetya, Johanes Adi (Edu Komputika Journal, 2024)
Advances in information and communication technology have changed the paradigm in the agricultural sector, especially in the application of the Internet of Things (IoT). An IoT-based monitoring system is an innovative step as there is an increasing need for technology in the agricultural sector and the development of the world of education. SMK Negeri 3 Salatiga, majoring in agribusiness, has great potential in hydroponic agriculture of lettuce plants, but there is no use of IoT technology in it. Hydroponic learning activities at SMK Negeri 3 Salatiga still use manual hydroponic learning media, which results in the competence possessed by teachers and students not being competent in IoT technology, especially its application to hydroponics. Meanwhile, if adjusted to learning outcomes, students should be able to fertilize plants in a modern way. The purpose of this study is to develop and implement hydroponic monitoring learning media based on Internet of Things technology. The application of learning media aims to improve the understanding or competence of teachers and students at SMK Negeri 3 Salatiga. The research methods used are Research and Development with the ADDIE development model, as well as one group pre-test and post-test design research design with 31 samples as a competency improvement test. This study resulted in 26 participants out of 31 participants experiencing an increase in competency in the results of the post-exam exam. So, it can be concluded that there is an increase in the competence of using hydroponic IoT by 83% among teachers and students.